2021
DOI: 10.3390/jcm10184221
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Incidence of Febrile Neutropenia among Patients Treated with Single-Agent Amrubicin: Necessity of the Primary Prophylactic Administration of Granulocyte Colony-Stimulating Factor

Abstract: Background: Single-agent amrubicin chemotherapy is a key regimen, especially for small cell lung cancer (SCLC); however, it can cause severe myelosuppression. Purpose: The purpose of this study was to determine the real-world incidence of febrile neutropenia (FN) among patients treated with single-agent amrubicin chemotherapy for thoracic malignancies. Patients and methods: The medical records of consecutive patients with thoracic malignancies, including SCLC and non-small cell lung cancer (NSCLC), who were tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Prophylactic granulocyte colony‐stimulating factor (G‐CSF) administration is recommended in AMR therapy for recurrent small cell lung cancer because of the high incidence of febrile neutropenia. 16 There was no significant difference in the incidence of febrile neutropenia between the study groups. However, febrile neutropenia could lead to deterioration of the patient's general condition and discontinuation of chemotherapy.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Prophylactic granulocyte colony‐stimulating factor (G‐CSF) administration is recommended in AMR therapy for recurrent small cell lung cancer because of the high incidence of febrile neutropenia. 16 There was no significant difference in the incidence of febrile neutropenia between the study groups. However, febrile neutropenia could lead to deterioration of the patient's general condition and discontinuation of chemotherapy.…”
Section: Discussionmentioning
confidence: 78%
“…In total, 21.2% of the patients developed febrile neutropenia. Prophylactic granulocyte colony‐stimulating factor (G‐CSF) administration is recommended in AMR therapy for recurrent small cell lung cancer because of the high incidence of febrile neutropenia 16 . There was no significant difference in the incidence of febrile neutropenia between the study groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a phase III study, which compared the efficacy of AP and that of IP in treatment naive Japanese patients with ED‐SCLC, the dose of AMR was reduced from 40 mg/m 2 to 35 mg/m 2 because of the high incidence of severe hematological toxicities 15 . Furthermore, our retrospective study revealed that the real‐world incidence rate of febrile neutropenia among patients with thoracic malignancies that were treated with single‐agent AMR chemotherapy was 30% 16 . Based on these findings for Japanese patients, the dose of 35 mg/m 2 AMR from second cycle to fourth is predicted as the suitable dose in this protocol.…”
Section: Discussionmentioning
confidence: 97%
“… 15 Furthermore, our retrospective study revealed that the real‐world incidence rate of febrile neutropenia among patients with thoracic malignancies that were treated with single‐agent AMR chemotherapy was 30%. 16 Based on these findings for Japanese patients, the dose of 35 mg/m 2 AMR from second cycle to fourth is predicted as the suitable dose in this protocol.…”
Section: Discussionmentioning
confidence: 97%